Fundus phenotype in retinitis pigmentosa associated with EYS mutations. (3rd September 2018) - Mucciolo, Dario Pasquale; Sodi, Andrea; Passerini, Ilaria; Murro, Vittoria; Cipollini, Francesca; Borg, Isabella; Pelo, Elisabetta; Contini, Elisa; Virgili, Gianni; Rizzo, Stanislao
ABSTRACT: Purpose : to report phenotypic and genotypic features in a group of autosomal recessive retinitis pigmentosa (arRP) patients associated with EYS mutations. Methods : we retrospectively reviewed the clinical records and the molecular genetic data of arRP patients carrying mutations in the EYS gene. All the patients underwent a comprehensive opthalmological examination. Additional investigation included color fundus photography, fundus autofluorescence, Goldmann visual field, OCT scans and full-field standard electroretinography. Results : we studied 10 RP patients (20 eyes) characterized by mutations in the EYS gene. Thirteen different sequence variants in the EYS gene were identified. In total, nine mutations found in our series had not previously been reported in the literature. All patients in our series complained of typical RP symptoms at the onset of the disease, namely night blindness and progressive constriction of the visual field. Visual acuity ranged from light perception to 20/20. Relevant findings reported in our series are Interdigitation-zone (IZ band) involvement, present even in the milder phenotypes and an estimated prevalence of 6.2% of arRP associated with EYS mutations. Conclusions : we reported the mutation spectrum of a group of EYS -related RP patients including nine novel mutations and the associated clinical phenotypes. Our series is the largest group of EYS -related arRP patients in the Italian population.